SISTEM TELEMETRI TINGKAT KONSENTRASI GAS CO2 SEBAGAI PENANGANAN DAMPAK GLOBAL WARMING BERBASIS MIKROKONROLER DENGAN INFORMASI SMS GATEWAY - Hadi Prasetyo Suseno; Muhammad Andang Novianta; Catur Iswahyudi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
The average temperature of global warming on the earth's surface today has increased by 0.74 ± 0:18°C, the increase was due to the increase in the average temperature of the atmosphere, ocean and land earth. Emissions of the most influential on the quality of the air is carbon emissions, especially carbon dioxide (CO2). The CO2 contributes to global warming is 50%. The CO2 gases absorb and reflect radiation emitted waves of the earth, so that the heat will be stored on the surface of the earth. This study aimed to design a data logger system monitoring the level of concentration of CO2 using the oxygen sensor (OOM202), carbon dioxide sensor (MG81), as well as temperature and humidity sensors (DHT22) with microcontroller-based SMS gateway information. The study tested are simulated in the laboratory with electronic testing and testing communication systems. The test results showed good performance with the prototype, the results of monitoring CO2 emissions seen huge levels of carbon dioxide (ppm) is proportional to the output voltage (Vout) is generated. The greater the concentration levels of gas detected by the sensor, the output voltage generated will be greater, than that difference or distinction ADC output between the measured and calculated because of several errors, such as error output ADC ± 2 bits, error rounding conversion of ADC to volt. The measurement results are different, in the closed and open area refers to the measurement parameters are displayed on an alphanumeric display. Measuring system can transmit data via SMS information system with an average response time of less than 1 minute, it depends on the quality of the signal and traffic data from a provider by the user.